The Image of the Modern Teacher and the Development of Pedagogical Skills (Journal of Educational Sciences, 2017)
The article considers the views of scientists on the image of the teacher and changes in the profession. If Ya.A.Comenskiy in the 17th century, figuratively compared the teacher with gardener, architect, sculptor and general, V. Levi in the 20th century have identified 36 roles in the activities of the teacher. Pedagogical skills of teachers are directly related to the ability to communicate, understanding and choosing your role-playing repertoire. The modern image of a teacher is based on competence approach. The purpose of this article is to compare current requirements to the teacher in psychological, pedagogical literature of Kazakhstan and abroad, design modern image, and determine the vector of development of pedagogical skills of the teacher. According to the students the important qualities are the honesty of the teacher, mutual understanding, sense of humor, patience, justice. The creation of a favorable creative atmosphere on the lesson is possible using sense of humor as a means of pedagogical skills of the teacher.Key words: teacher image, pedagogical skills, sense of proportion, the virtue of moderation, competence of a teacher, the humor in pedagogical activity.